Pengaruh Dewan Direksi Dan Komisaris Independen Terhadap Pengungkapan Sustainability Report - Tafkiyatul Cindy Aulia; Dirvi Surya Abbas; Reni Anggraeni (International Forum of Researchers and Lecturers, 2023)
The purpose of this study is to determine the influence of independent boards of directors and commissioners on the disclosure of sustainability reports on mining companies listed on the Indonesia Stock Exchange (IDX). The research time period used is 4 years, namely the 2018-2021 period. The population in this study includes all mining companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. The sampling technique uses purposive sampling techniques. Based on the criteria that have been set in the acquisition of 10 companies. The type of data used is secondary data obtained from www.idx.co.id site, the analysis method used is panel data regression analysis. The results of this study show that the board of directors has an effect on the disclosure of the sustainability report, then the independent commissioner has an effect on the disclosure of the sustainability report.